Identification of the Physical Characteristics of Microplastics in Biota in Musi River Waters - Casmita, Khansa Shafa; Windusari, Yuanita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Microplastics are plastic waste in the environment which, over a long period of time, will decompose into micro particles or smaller sizes. Microplastics have various types of shapes, sizes and colors which are influenced by various factors. Over time, microplastics in river waters will pollute the biota in the river. Humans who consume microplastics indirectly by consuming fish from rivers that have been polluted with microplastics have the potential to cause side effects. This research aims to identify microplastics in fish biota in the waters of the Musi River in Banyuasin Regency. This research is descriptive analytical in nature with a sampling technique, namely random sampling, namely the technique of taking fish at random. The sample research went through several stages, namely sample preparation, digestion, filtration and research with a trinocular microscope. This research is descriptive analytical in nature with a sampling technique, namely random sampling, namely the technique of taking fish at random. The sample research went through several stages, namely sample preparation, digestion, filtration and research with a trinocular microscope. Identification of microplastics in biota in the waters of the Musi River (downstream) in the Banyuasin Regency area found microplastics in the form of fiber, foam and fragments which were dominated by fiber form. The colors of the microplastics found were green and brown. The largest size of microplastic is 1068.92µm and the smallest is 306.46µm.